2018
DOI: 10.22214/ijraset.2018.3562
|View full text |Cite
|
Sign up to set email alerts
|

Study on Photoconductivity in Air and Vacuum of ZnO Prepared by different materials

Abstract: O] was used as precursor to prepare zinc oxide by thermal decomposition method. Its photoconductivity and dark-conductivity properties have been studied in air as well as in vacuum. Voltage dependence of photocurrent and dark-current has been observed at room temperature in air under UV-vis illumination. Stuructural study of ZnO microstructures has been analyzed by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Rise and decay curve in air exhibits anomalous behavior wherein the photocurrent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Under UV light, Saxena et al demonstrated a higher photocurrent in vacuum than in air from ZnO microstructures. Similarly, their current decay time in dark was found to be higher in vacuum than in air [55]. Furthermore, Bao et al studied the photoconductivity of ZnO nanowires in vacuum by radiating the ZnO nanowire with three different power sources of UV radiation for 5 h, until saturation photocurrent was reached.…”
Section: Electrical and Optoelectrical Properties Of Zno Nanorodsmentioning
confidence: 99%
“…Under UV light, Saxena et al demonstrated a higher photocurrent in vacuum than in air from ZnO microstructures. Similarly, their current decay time in dark was found to be higher in vacuum than in air [55]. Furthermore, Bao et al studied the photoconductivity of ZnO nanowires in vacuum by radiating the ZnO nanowire with three different power sources of UV radiation for 5 h, until saturation photocurrent was reached.…”
Section: Electrical and Optoelectrical Properties Of Zno Nanorodsmentioning
confidence: 99%